2020
DOI: 10.1371/journal.pone.0231151
|View full text |Cite
|
Sign up to set email alerts
|

What is the difference between perceived and actual risk of distracted driving? A field study on a real highway

Abstract: Distracted driving is a leading cause of traffic accidents. It is influenced by driver attitude toward secondary tasks; however, field-based studies on the effects of low-perceived-risk tasks on lateral driving have rarely been reported. A total of 17 experienced non-professional drivers were recruited to participate in two secondary tasks: a cognitive experiment (conversation) and a visual distraction experiment (observation of following vehicles), each representing low-perceived-risk secondary tasks. One-way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…"Naturalistic driving study" (NDS) provides insight into this issue under natural driving conditions [71]. "On-road test" is a middle way of simulation and NDS: similar to NDSs, participants engage in real driving tasks; similar to simulation, non-driving tasks are assigned by experimenters [72,73]. Furthermore, the two epidemiological methods, "observational study" and "questionnaire survey", reflect social behaviors and public opinions in time and thus support subsequent technological development, educational campaign and legislation [74,75].…”
Section: Plos Onementioning
confidence: 99%
“…"Naturalistic driving study" (NDS) provides insight into this issue under natural driving conditions [71]. "On-road test" is a middle way of simulation and NDS: similar to NDSs, participants engage in real driving tasks; similar to simulation, non-driving tasks are assigned by experimenters [72,73]. Furthermore, the two epidemiological methods, "observational study" and "questionnaire survey", reflect social behaviors and public opinions in time and thus support subsequent technological development, educational campaign and legislation [74,75].…”
Section: Plos Onementioning
confidence: 99%
“…Motion demands include task completion time (TCT) as well as the duration of time hands are off the steering wheel. A large number of driving simulator-based experiments have been conducted to show that as a secondary task takes up more visual resources and as TCT increases, lateral driving performance will be worse, and the risk of lane departure will increase significantly [15][16][17].…”
Section: Research On the Impact Of Secondary Tasks On Resourcementioning
confidence: 99%
“…About 1.3 million lives are ended as a result of road traffic accidents every year, and a range of 20–50 million people suffer injuries and disability [ 1 ]. It is reported that the majority of road traffic accidents are contributed to drivers, and distracted driving is the most important contributing factor [ 2 ].…”
Section: Introductionmentioning
confidence: 99%